Rehabilitation Augments Hematoma Clearance and Attenuates Oxidative Injury and Ion Dyshomeostasis After Brain Hemorrhage. Issue 1 (January 2017) - Williamson, Michael R.; Dietrich, Kristen; Hackett, Mark J.; Caine, Sally; Nadeau, Colby A.; Aziz, Jasmine R.; Nichol, Helen; Paterson, Phyllis G.; Colbourne, Frederick
Abstract : Background and Purpose—: We assessed the elemental and biochemical effects of rehabilitation after intracerebral hemorrhage, with emphasis on iron-mediated oxidative stress, using a novel multimodal biospectroscopic imaging approach. Methods—: Collagenase-induced striatal hemorrhage was produced in rats that were randomized to enriched rehabilitation or control intervention starting on day 7. Animals were euthanized on day 14 or 21, a period of ongoing cell death. We used biospectroscopic imaging techniques to precisely determine elemental and molecular changes on day 14. Hemoglobin content was assessed with resonance Raman spectroscopy. X-ray fluorescence imaging mapped iron, chlorine, potassium, calcium, and zinc. Protein aggregation, a marker of oxidative stress, and the distribution of other macromolecules were assessed with Fourier transform infrared imaging. A second study estimated hematoma volume with a spectrophotometric assay at 21 days. Results—: In the first experiment, rehabilitation reduced hematoma hemoglobin content ( P =0.004) and the amount of peri-hematoma iron ( P <0.001). Oxidative damage was highly localized at the hematoma/peri-hematoma border and was decreased by rehabilitation ( P =0.004). Lipid content in the peri-hematoma zone was increased by rehabilitation ( P =0.016). Rehabilitation reduced the size of calcium deposits ( P =0.040) and attenuated persistent dyshomeostasis of Cl − ( P <0.001) but not K + ( P =0.060). The second study confirmed that rehabilitation decreased hematoma volume ( P =0.024). Conclusions—: Rehabilitation accelerated clearance of toxic blood components and decreased chronic oxidative stress. As well, rehabilitation attenuated persistent ion dyshomeostasis. These novel effects may underlie rehabilitation-induced neuroprotection and improved recovery of function. Pharmacotherapies targeting these mechanisms may further improve outcome.